2014
DOI: 10.4103/0022-3859.132309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nutritional status of rural and urban school students receiving midday meals in schools of Bengaluru, India

Abstract: Greater involvement of the private sector to assist the government would help augment nutrition in children and indirectly impact school performance, attendance and literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The anthropometric characteristics of all participants across the three trial arms at baseline were similar. Prevalence of stunting (10%) and underweight (18%) were comparable to those reported in rural schoolchildren aged 5-14 years from Bengaluru (17% stunting and 17% underweight) [41].…”
Section: Discussionsupporting
confidence: 61%
“…The anthropometric characteristics of all participants across the three trial arms at baseline were similar. Prevalence of stunting (10%) and underweight (18%) were comparable to those reported in rural schoolchildren aged 5-14 years from Bengaluru (17% stunting and 17% underweight) [41].…”
Section: Discussionsupporting
confidence: 61%
“…School meals programs are widely considered as one of the most effective interventions to simultaneously improve nutrition and education outcomes for schoolchildren in developing countries [5]. School meals programs contribute to alleviating short-term hunger in schoolchildren, which increases their ability to concentrate and learn while they are at school [6,7]. Such programs also increase student enrolment, attendance and retention rates [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done in Rural and Urban areas of Bangalore 18 among mid day meal beneficiaries, it was found that the prevalence of undernutrition was 13.8% and in a study done in Mangalore 19 it was observed that prevalence of thinness among female students was 15.8%. These studies showed less prevalence than the present study.…”
Section: Discussionmentioning
confidence: 96%